Efektifitas Pembuatan Nasi Instan dengan Membandingkan Metode Rendam-Kukus-Keringkan dan Metode Freeze Drying Sebagai Alternatif Pangan Darurat Korban Bencana - Dini Rudini; Andi Subandi; Muhammad Nasril Lukman (Universitas Pahlawan Tuanku Tambusai, 2023)
Indonesia is one of the most disaster-prone countries. Food is one of the mandatory things that become a necessity with any condition, so instant rice is needed with about 5 minutes ready for consumption. The methods that are often used are the Soak-Steam-Dry and Freeze Drying methods. Method: This study used quantitative experimental design. The first is preliminary research, the second compares the two most effective and efficient manufacturing methods to be applied in times of disaster and the third is nutritional analysis on two manufacturing methods. Results: The results of the Soaking Steam-Dry method have faster results for producing instant rice than freeze drying where the Soaking Steaming dry method takes 16 hours 12 minutes to make while Freeze Drying takes 22 hours 40 minutes to make. So the Soak-Steam-Dry method is more effective for producing instant rice. Conclusion: There is a difference in the effectiveness of making instant rice between the Soak-Steam-Dry method and the Freeze Drying method, where the Soak-Steam-Dry method is more effective than the Freeze Drying method